Comparison of thermal runaway limits under different test conditions based on a 4.5 kV IGBT. (September 2016) - Reigosa, P.D.; Prindle, D.; Pâques, G.; Geissmann, S.; Iannuzzo, F.; Kopta, A.; Rahimo, M.
Abstract: This investigation focuses on determining the temperature-dependent leakage current limits which compromise the blocking safe operating area for silicon IGBT technologies. A discussion of a proper characterization method for selecting the maximum rated junction temperature for devices operating at high temperatures is given by comparing the different testing methods: Static performance (including and excluding self-heating effects), Short Circuit Safe Operating area and High-Temperature Reverse Bias. Additionally, a thermal model is used to predict the junction temperature at which thermal runaway takes place. In this paper guidelines are proposed based on the correlation among short circuit withstand capability and off-state leakage current for guarantying reliable operation and ensuring that they are thermally stable under parameter variations. This study is helpful to facilitate application engineers for defining the correct stability criteria and/or margins in respect of thermal runaway.